2023
DOI: 10.1111/clr.14133
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiographic outcomes of zirconia dental implants—A systematic review and meta‐analysis

S. Roehling,
M. Gahlert,
M. Bacevic
et al.

Abstract: ObjectivesFor the present review, the following focused question was addressed: In patients with root‐analog dental implants, what is the effect of implants made of other materials than titanium (alloy) on implant survival, marginal bone loss (MBL), and technical and biological complications after at least 5 years.Materials and MethodsAn electronic (Medline, Embase, Web of Science) search was performed to identify observational clinical studies published from January 2000 investigating a minimum of 20 commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…While a 2023 systematic review and meta-analysis has concluded that commercially available zirconia implants demonstrated reliable clinical outcomes based on survival rates, pocket depth, and MBL values, most of their studies investigated one-piece zirconia implants [76]. In fact, only one study reported technical complications with the two-piece zirconia implants (six fractures of 48 fiberglass abutments over 53.7 months) [65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While a 2023 systematic review and meta-analysis has concluded that commercially available zirconia implants demonstrated reliable clinical outcomes based on survival rates, pocket depth, and MBL values, most of their studies investigated one-piece zirconia implants [76]. In fact, only one study reported technical complications with the two-piece zirconia implants (six fractures of 48 fiberglass abutments over 53.7 months) [65].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, only one study reported technical complications with the two-piece zirconia implants (six fractures of 48 fiberglass abutments over 53.7 months) [65]. The systematic review authors also noted that at the onset of 2004, the first zirconia implants were established on the market, and many were replaced with a total of 16 current manufacturers [76]. The top manufacturers today are Straumann, Nobel Biocare, Dentsply, ZimVie, Osteem, Stryker, Smith and Nephew, Integrum, and Southern Implants.…”
Section: Discussionmentioning
confidence: 99%
“…How to cite this article: Laleman, I., Lambert, F., Gahlert, M., Bacevic, M., Woelfler, H., & Roehling, S. (2023). The effect of different abutment materials on peri-implant tissues-A systematic review and meta-analysis.…”
Section: Co N Fli C T O F I Nte R E S T S Tate M E Ntmentioning
confidence: 99%
“…This focused question was thus answered in two separate systematic reviews. One focused on the effect of implant materials on the peri-implant tissues in clinical trials (here, we want to cite the other systematic review about implants: Roehling S. et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…As of 2017, many questions on the use of zirconia for dental implants were still unanswered [ 18 , 19 ]. A review on the subject was recently published [ 20 ], although with very restricted inclusion criteria, which limited the number of included studies. Moreover, survival analysis of zirconia implants in relation to preparation or not of their coronal part with drills, as well as in relation to implants discontinued from the market or still commercially available, was not performed.…”
Section: Introductionmentioning
confidence: 99%